ANALISIS KESULITAN BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS VI SD KARTIKA XIX/7 KOTA CIREBON - Rusdin, Muhammad; Pratiwi Dwi Santi, Dina (Department of Mathematics Education, Universitas Kuningan, 2025)
Students' learning difficulties in learning flat shape mathematics are the main phenomenon underlying this research. This research aims to examine and describe students' learning difficulties and the causes of students experiencing learning difficulties in learning flat shape mathematics. The subjects in this research were 10 class VI students at Kartika XIX/7 Elementary School, Cirebon City. The research subjects were taken using the Purposive Sampling method. The type of research used is descriptive qualitative. Data collection uses test instruments in the form of essay questions and non-test instruments in the form of interviews. The data analysis technique in research consists of three stages, namely data reduction, data presentation and drawing conclusions. This research was also carried out in three stages which included the preparation stage, research implementation stage, and completion stage. The results of this research show that students' learning difficulties in plane material were analyzed using the Van Hiele level of thinking. The data shows that the majority of students experience difficulties at the deduction (82%) and rigor (82%) levels. Meanwhile, difficulties at the level of visualization (8%), analysis (10%), and informal deduction (6%) were relatively lower.